Combined apocyanin and aspirin treatment activates the PI3K/Nrf2/HO-1 signaling pathway and ameliorates preeclampsia symptoms in rats. (2nd January 2022) - Ju, Yaru; Feng, Yan; Hou, Xiaolin; Wu, Lixia; Yang, Huixia; Zhang, Hongjuan; Ma, Yan'Na
ABSTRACT: Objective: Pre-eclampsia (PE) is a pregnancy-associated disease characterized by placental dysfunction and increased oxidative stress. Apocyanin is a potent antioxidant and anti-inflammatory which has shown beneficial effects on PE pathogenesis. Aspirin is recognized as the recommendable drug in PE prevention and therapy. Therefore, we aimed to investigate the effects of combining apocyanin and aspirin to treat PE on rat models induced by N-nitro-L-arginine methyl ester (L-NAME) from gestational day (GD) 6 to 16 and elucidate the potential mechanisms. Methods: First, female pregnant rats were divided into five different groups: pregnant control, PE, PE + apocyanin, PE + aspirin, and PE + apocyanin + aspirin. Animals received apocyanin (16 mg/kg/day) orally or aspirin by gavage (1.5 mg/kg BM/day) from GD 4 to 16. Blood pressure and urine protein content were monitored every 4 days. Results: In the PE rat model, elevated systolic blood pressure and proteinuria were ameliorated by the combination of apocyanin and aspirin. Meanwhile, compared with single-dose apocyanin or aspirin, the combined treatment significantly corrected abnormal pregnancy outcomes, decreased sFlt-1 and PlGF, and alleviated oxidative stress both in blood and placental tissues. Moreover, the combined treatment upregulated PI3K, Akt, Nrf2, and HO-1 protein levels in the placental tissues from PE rats. Conclusion: Overall, our results suggested that combined treatment of apocyanin and aspirin ameliorates the PE symptoms compared with single-dose apocyanin or aspirin in a PE rat model. Also, we demonstrated that activating the PI3K/Nrf2/HO-1 pathway can be a valuable therapeutic target to improve the pregnancy outcomes of PE.